A flexible data‐driven approach to co‐producing drought vulnerability assessments - Shelley D. Crausbay; Kimberly R. Hall; Molly S. Cross; Meghan Halabisky; Imtiaz Rangwala; Jesse Anderson; Ann Schwend (Ecosphere, 2024)
Abstract Intensifying weather events are key characteristics of climate change that are fundamentally changing ecological disturbance regimes. Intensifying drought is a particular threat to species, ecosystems, and ecosystem services worldwide. Proactive drought adaptation measures are acutely needed, but without a better understanding of drought vulnerability at the appropriate scale and geography, such measures may not be effective, or even anticipated as potential options. A recent conceptual framework for ecological drought aligns a holistic suite of potential drivers with the key components of climate change vulnerability (exposure, sensitivity, and adaptive capacity). We leverage the ecological drought framework and components of vulnerability to introduce a six‐step process for developing a drought vulnerability assessment (DVA) that (1) is place‐based and avoids mismatches between assessment geography and management action, (2) uses existing empirical datasets and leverages machine learning techniques and remotely sensed data from a recent drought, (3) emphasizes the inclusion of stakeholders and the importance of data visualization and science communication, and (4) is flexible and adaptable to a wide range of planning contexts. We illustrate the DVA process with a case study for forested watersheds in the Missouri Headwaters (MH), Montana, USA, that is focused on the impact of an early 2000s drought event on forest health. We show how the DVA provides insights on drought vulnerability that are helpful starting points for co‐developing region‐specific management actions to prepare for the next drought, including strategies to enhance ecologically available water, reduce competition for water, promote ecosystem persistence under drought conditions, and prioritize sites for forest restoration, transition, or protection. The work described here provides a model for developing a DVA in other places that, when used in a participatory adaptation planning process, supports the implementation of effective adaptation strategies.